MYC Negative Rectal B-Cell Lymphoma, Unclassifiable, with Features Intermediate between Diffuse Large B-Cell Lymphoma and Burkitt’s Lymphoma in an Immunocompetent Patient - Jignesh G. Parikh; Ted Strom; Ilya Stone (Case Reports in Pathology)
B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma and Burkitt’s lymphoma (BLUI) is a recently added entity to the World Health Organization (WHO) classification to address a grey zone between large B-cell lymphoma (DLBCL) and Burkitt’s lymphoma (BL). These are rare aggressive lymphomas, which were previously also known as Burkitt’s-like lymphoma (BLL). BL and BLUI/BLL of the colon mostly involve the ileocecal region. In the rectum, BL and BLUI/BLL almost always affect patients with the acquired immune deficiency syndrome (AIDS). We report the first case of rectal BLUI/BLL in an immunocompetent patient who is also negative for MYC abnormalities and the EBV early RNA (EBER) in situ hybridization.